Blank canvas or under construction? Examining the pre-academy experiences of young developing professional team sports athletes - Foivos Papastaikoudis; Rosie Collins; Rosie Collins; Dave Collins; Dave Collins (Frontiers Media S.A., 2023)
IntroductionExtensive research has been carried out on Talent Development (TD) environments and an increasing amount of work shows the development of psychological characteristics as an important formal part of the academy experience. Importantly, however, very little attention has been paid to what types of skills, if any, young players arrive with. In other words, there seems to be an assumption that young athletes arrive at the academy as a blank canvas.MethodsAs such, to investigate whether players' arrive with these psychological characteristics, we looked across a sample of young footballers' and rugby players' personal experiences (such as, family input, sporting background or personal challenges) prior joining the academy. Individual semi-structured interviews were conducted, and data were analysed via thematic analysis.ResultsOur findings suggested that young athletes acquired an aptitude from general experiences, whereby they had already started to develop and deploy specific skills (such as, reflective practice, mental skills or seeking social support) to navigate particular challenges, prior to arriving at the academy.ConclusionImplications include the need for coaches and psychologists to assess young athletes' skillsets and pre-academy experiences upon arrival and use this as a starting point for developing tailored and individualised pathways that would enable them maximise their potential.